Establishment of a patient‐derived xenograft model and cell line of malignant transformation of mature cystic teratoma of the ovary. Issue 2 (9th December 2020) - Tamauchi, Satoshi; Suzuki, Shiro; Xuboya, Chang; Yoshihara, Masato; Yoshida, Kosuke; Ikeda, Yoshiki; Yoshikawa, Nobuhisa; Kajiyama, Hiroaki; Kikkawa, Fumitaka
Abstract: Aim: Malignant transformation of mature cystic teratoma (MTMCT) of the ovary is a rare gynecological malignancy and commonly arises in women older than 50 years of age. The most common histological type of MTMCT is squamous cell carcinoma (SCC), and the prognosis is extremely poor. Patient‐derived xenograft (PDX) models are promising animal models for preclinical drug screening. Here, we report the generation of a new PDX model of MTMCT, and a new cell line established from the tumors of PDX model animals. Methods: Tumor tissue was obtained from a 32‐year‐old patient with MTMCT. To generate PDX, NSG (NOD.Cg‐Prkdc scid Il2rg tm1Wjl /SzJ) mice, a strain of super‐immunodeficient mice, were used. Tumor‐bearing mice were sacrificed, followed by the collection of these tumors and re‐transplantation into new NSG mice ( in vivo passage). Tumor samples were also cultured in vitro . Adherent cells were continuously cultured and passaged, a cell line was established. Results: In the primary PDX mouse, tumor engraftment was confirmed 30 days after tumor implantation. After three times in vivo passage, we confirmed that the cryopreserved tumors could be engrafted even when transplanted into BALB/c nude mice. Using the tumor tissue at the time of the first in vivo passage, a new cell line NOSCC1 was established. PDX tumors and cell‐line derived xenograft tumors exhibited similar morphology of SCC. Conclusion: We established a new PDX model of MTMCT and a new cell line of it, which may be important tools for the development of new therapies and the elucidation of the carcinogenic mechanisms of MTMCT.